"I Could Have Stood a Little More Education Rather than Just: 'Hey, you're Diabetic Man, Make the Best out of It'": Revisioning Diabetes Self-Management Education for Older Adults. (July 2023) - Robertson, Madison; Paré, Geneviève C.; Costa, Idevania; Alvarado, Beatriz; Duhn, Lenora; Plazas, Pilar Camargo
Objectives: Providing diabetes self-management education (DSME) in an evidence-based format that is accessible and tailored to the population needs is crucial for individuals living with diabetes mellitus. Our qualitative study explores the experiences of older adults living with diabetes while residing in a rural setting.Methods: Adults aged 65 or older and residing in a rural area of Ontario completed a photovoice activity and semi-structured interviews to illustrate their experience of living with diabetes and accessing DSME.Results: Fourteen participants (11 males; mean age = 74 years) completed the photovoice activity and interview. Four main themes were identified pertaining to learning about diabetes education, the depth and breadth of learning, applying knowledge to daily life, and engaging older adults in DSME.Discussion: Diabetes self-management education should account for older adults' preferences in learning about diabetes and self-management to promote access to evidence-based information, bolster knowledge and self-management efficacy, and improve disease control.